Analisa Strategi Diversity Analytic Pada Suatu Perusahaan - Calvin; Julius Kurnaedi; Jimmy Lim; Rano Ardiansyah; Alden Nelson (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Human resources are one of the important resources in a company because they affect the productivity of a company, every company must have human resources with ethnic, racial, religious and gender diversity so that they need to be managed properly so that they can run effectively and efficiently for the company. This study uses descriptive qualitative data methods by making in-depth observations of the research using qualitative data. The results of this study indicate that the importance of the DEI strategy (diversity, equity, inclusion) is applied to a company in order to unify the diversity that exists in the company and create a comfortable work environment and equality for each employee against the applicable company norms and policies.